Supply, commissioning and post implementation support of core network with 3 years warranty for the Brac University new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and BRACNet Limited to supply, commissioning and post implementation support of core network with 3 years warranty for the Brac University new campus project.